Perfil epidemiológico de acidentes com material biológico entre estudantes de medicina em um pronto-socorro cirúrgico - Reis, Phillipe Geraldo Teixeira De Abreu [UNESP] (2013)
OBJECTIVE: To evaluate the accidents with biological material among medical students interning in a trauma emergency room and identify key related situations, attributed causes and prevention. METHODS: we conducted a study with a quantitative approach. Data were collected through a questionnaire applied via internet, with closed, multiple-choice questions regarding accidents with biological material. The sample comprised 100 students. RESULTS: thirty-two had accidents with biological material. Higher-risk activities were local anesthesia (39.47%), suture (18.42%) and needle recapping (15.79%). The main routes of exposure to biological material were the eyes or mucosa, with 34%, and syringe needle puncture, with 45%. After contamination, only 52% reported the accident to the responsible department. CONCLUSION: The main causes of accidents and routes of exposure found may be attributed to several factors, such as lack of training and failure to use personal protective equipment. Educational and preventive actions are extremely important to reduce the incidence of accidents with biological materials and improve the conduct of post-exposure. It is important to understand the main causes attributed and situations related, so as general and effective measures can be applied.